2002
DOI: 10.1103/physrevlett.88.037603
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Edge Localized Moments in the Doped Spin-Peierls SystemCuGe1xSixO<

Abstract: We report the observation of nuclear quadrupole resonance (NQR) of Cu from the sites near the doping center in the spin-Peierls system CuGe 1-xSixO3. The signal appears as the satellites in the Cu NQR spectrum, and has a suppressed nuclear spin-lattice relaxation rate indicative of a singlet correlation rather than an enhanced magnetic correlation near the doping center. Signal loss of Cu nuclei with no neighboring Si is also observed. We conclude from these observations that the doping-induced moments are not… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
0
14
1
1
Order By: Relevance
“…Furthermore, if isolated spins were present and acted as relaxation centers, then the relaxation curve would have to be a stretched-exponential type function as is often reported in dilute magnetic alloys 38,39 or doped spin-Peierls systems. 40,41 In fact, the observed relaxation always obeyed a simple-exponential-type function over the entire range of experimental temperatures and fields ͑as stated above͒ assuring that the island picture is plausible.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, if isolated spins were present and acted as relaxation centers, then the relaxation curve would have to be a stretched-exponential type function as is often reported in dilute magnetic alloys 38,39 or doped spin-Peierls systems. 40,41 In fact, the observed relaxation always obeyed a simple-exponential-type function over the entire range of experimental temperatures and fields ͑as stated above͒ assuring that the island picture is plausible.…”
Section: Discussionmentioning
confidence: 82%
“…In the spin-Peierls compound CuGe 1−x Si x O 3 , which is effectively a bonddisorder Heisenberg antiferromagnet, 2 it was experimentally observed that the effective spins are induced not near Si impurity sites but rather at sites between them in the AF LRO phase. 9 The occurrence of the AF LRO is then attributed to the nonlocal reconstruction of bond alternation by Si substitution. To understand this type of phase transitions in the spin-Peierls state, we have to analyze models with proper spin-lattice coupling, which will be another challenging numerical work in near future.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Such an impurity-induced AF LRO has been observed also in the bond-disorder system, CuGe 1−x Si x O 3 . 2,8,9 In early theoretical and numerical studies on quasi-one-dimensional diluted Heisenberg antiferromagnets, the effect of inter-chain interaction is often taken into account by making use of meanfield approximations, where the site and bond dilutions are unable to be distinguished with each other. [10][11][12] By the recent numerical analyses, however, the characteristic feature of the site-dilution-induced AF LRO has been understood more clearly by treating the inter-and intrachain interactions on an equal footing.…”
Section: Introductionmentioning
confidence: 99%
“…Ces résultats pourraient être compatibles avec l'apparition d'une aimantation alternée, sans qu'on puisse conclure la forme de la polarisation. D'autres mesures par NQR pour une substitution hors de la chaine (au Si) démontrent que l'aimantation induite a un maximum loin du défaut Si comme pour un soliton ( fig.c) (Kikuchi, 2002). L'existence et la forme d'une structure solitonique a été mesurée directement par RMN, non pas induit par impuretés mais lié à l'application d'un champ très intense .…”
Section: Impuretés Dans Les Chaînes De Spin ½unclassified